A STUDY OF THE APPLICATION OF THE CONCEPT OF INTEGRATION-INTERCONNECTION OF ISLAMIC-BASED LOGOTHERAPY IN ISLAMIC GUIDANCE AND COUNSELING - Rara Eka Yurika; Irsyadunnas Irsyadunnas (Al-Tazkiah Jurnal Bimbingan dan Konseling Islam, 2024)
This study examines the application of integration and interconnection in Islamic-based logotherapy in Islamic guidance and counseling. The research method used was library research. The results of this study are three main concepts of logotherapy that were integrated and interconnected with Islamic concepts, namely regarding ten theses about humans and Islamic views of humans, Frankl's noös approach and spiritual understanding in Islam, and human goals according to Frankl and human goals according to Islam. The implementation of Islam-based logotherapy in the implementation of Islamic guidance and counseling can be applied using worship therapy.  The conclusion of this research shows that the integration-interconnection of logotherapy with Islamic concepts in Islamic guidance and counseling can be applied.